Socrates in the fMRI Scanner: The Neurofoundations of Morality and the Challenge to Ethics - Rueda, Jon (Cambridge quarterly of healthcare ethics, 2021)
The neuroscience of ethics is allegedly having a double impact. First, it is transforming the view of human morality through the discovery of the neurobiological underpinnings that influence moral behavior. Second, some neuroscientific findings are radically challenging traditional views on normative ethics. Both claims have some truth but are also overstated. In this article, the author shows that they can be understood together, although with different caveats, under the label of “neurofoundationalism.” Whereas the neuroscientific picture of human morality is undoubtedly valuable if we avoid neuroessentialistic portraits, the empirical disruption of normative ethics seems less plausible. The neuroscience of morality, however, is providing relevant evidence that any empirically informed ethical theory needs to critically consider. Although neuroethics is not going to bridge the is–ought divide, it may establish certain facts that require us to rethink the way we achieve our ethical aspirations.